Crecimiento de Eucalyptus grandis hasta los 11 años a partir de diferentes densidades iniciales de plantación en el noroeste de Misiones, Argentina = Growth of Eucalyptus grandis up to 11 years from different initial planting densities in northwestern Misiones, Argentina - Keller, Aldo Esteban (2023)
Eucalyptus grandis is a species with great potential to be cultivated in the region. From a trial of initial planting densities, with 3 completely randomized blocks and 4 levels of density (defined as 2500, 1250, 625 and 312 trees per hectare), differences in growth were observed. While diameter at breast height and survival were inversely proportional to the density total volume were proportional to plantation density with mean annual increases in volume varied between 60 m3ha-1year-1 and 24 m3ha-1year-1, between the highest and lowest density, respectively.